2015
DOI: 10.1002/macp.201500104
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Mediated Reactions in Photopolymerizable Radical Thin Films: Application to Simultaneous Photocuring Under Air and Nanoparticle Formation

Abstract: Titanium propoxide, titanium isopropoxide, and titanium (triethanolaminato) isopropoxide are proposed as high‐performance additives to overcome the oxygen inhibition effects in the free radical photopolymerization of a low‐viscosity monomer thin film, under air and upon a low‐intensity UV light activation. Indeed, when added to a Type I photoinitiator such as bis(2,4,6‐trimethylbenzoyl)‐phenylphosphine oxide (BAPO), noticeably higher conversions are achieved under air (48% vs. 30%). The in situ formation of Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…In a previous investigation, we also demonstrated that the use of titanium alkoxides, 34 namely, titanium isopropoxide or titanium (triethanolaminato) isopropoxide precursors, with a UV-cleavable photoinitiator (bis(2,4,6-trimethylbenzoyl)-phenylphosphineoxide, BAPO) appears to be efficient photoinitiating systems that overcome the oxygen inhibition effects in free-radical photopolymerization of TMPTA. These systems under air and upon exposure to a low-intensity UV light activation result in simultaneous formation of Ti-based NPs.…”
Section: ■ Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a previous investigation, we also demonstrated that the use of titanium alkoxides, 34 namely, titanium isopropoxide or titanium (triethanolaminato) isopropoxide precursors, with a UV-cleavable photoinitiator (bis(2,4,6-trimethylbenzoyl)-phenylphosphineoxide, BAPO) appears to be efficient photoinitiating systems that overcome the oxygen inhibition effects in free-radical photopolymerization of TMPTA. These systems under air and upon exposure to a low-intensity UV light activation result in simultaneous formation of Ti-based NPs.…”
Section: ■ Introductionmentioning
confidence: 89%
“…For example, we demonstrated that the addition of peroxyls to Cp 2 ZrCl 2 ( 2 ) leads to the formation of cyclopentadienyl radicals (Cp • ), which readily initiate the free-radical polymerization of TMPTA ( 3 ). The successive addition of peroxyls to putative CpZrCl 2 (OOR) has been shown to be responsible for the in situ generation of Zr-based NPs ( 4 ). In a previous investigation, we also demonstrated that the use of titanium alkoxides, namely, titanium isopropoxide or titanium (triethanolaminato) isopropoxide precursors, with a UV-cleavable photoinitiator (bis­(2,4,6-trimethylbenzoyl)-phenylphosphineoxide, BAPO) appears to be efficient photoinitiating systems that overcome the oxygen inhibition effects in free-radical photopolymerization of TMPTA. These systems under air and upon exposure to a low-intensity UV light activation result in simultaneous formation of Ti-based NPs.…”
Section: Introductionmentioning
confidence: 99%
“…356−358 In a quite similar approach, they investigated a series of different Ti-based complexes containing Ti−O bonds as additives toward reduction of oxygen inhibition for the free radical polymerization initiated by a bisacylphosphine oxide photoinitiator, as well as photochemical generation of metallic nanoparticles. 359,360 The key to these systems is the formation of metal-based radical compounds which act as peroxyl radical scavengers, and multiple addition of peroxyl radicals leads to the formation of metal nanoparticles.…”
Section: Polymer-metal Nanocomposites Bymentioning
confidence: 99%
“…Thus, significant enhancement of the rate of polymerization in the presence of oxygen was achieved by the added organometallic compounds being used as additives to Type I photoinitiators. The interaction of the peroxyl radicals with the organometallic compounds through a bimolecular homolytic substitution reaction led to the formation of metal-based structures, which finally resulted in the generation of metallic nanoparticles embedded in the polymeric matrix. In a quite similar approach, they investigated a series of different Ti-based complexes containing Ti–O bonds as additives toward reduction of oxygen inhibition for the free radical polymerization initiated by a bisacylphosphine oxide photoinitiator, as well as photochemical generation of metallic nanoparticles. , The key to these systems is the formation of metal-based radical compounds which act as peroxyl radical scavengers, and multiple addition of peroxyl radicals leads to the formation of metal nanoparticles.…”
Section: Polymer-metal Nanocomposites By Photoinduced Electron Transf...mentioning
confidence: 99%
“…In Figure 14, during the illuminated part of each cycle of modulation, the electromagnetic radiation ( hν ) is absorbed by the epoxy diacrylate system (epoxy diacrylate resin+photoinitiator). The α‐cleavage is the main radiation less de‐excitation for the photoinitiator molecules, 37 which produces free radicals that can react with: (i) oxygen uptake from the photoacoustic chamber (PA) (air), giving rise a decreasing pressure in the PA chamber (photobar component of the PAS signal); and (ii) polymer chain in the polymerization process, where the heat generated diffuse to the sample/air interface that heat the bordering air given rise an increasing pressure in the PA chamber (exother component of the PAS signal). For the epoxy diacrylate resin (unlinked, PAS1, and linked polymer chain, PAS2), the main radiationless de‐excitation is the thermal relaxation, which produces heat that diffuse to the sample/air interface that heat the bordering air given rise an increasing pressure in the PA chamber (PAS1 and PAS2 components of the PAS signal).…”
Section: Resultsmentioning
confidence: 99%